Profil Kemampuan Berpikir Abstrak Siswa SMP dalam Memecahkan Masalah Matematika Ditinjau dari Adversity Quotient - Dinda Putri Rubiyanti; Pradnyo Wijayanti (MATHEdunesa, 2023)
Abstract thinking ability is a person’s ability of someone to represent problems in the form of mathematical models and relate them to concepts to find solutions to existing problems. The succes of students in solving problems also depends on intelligence of students in dealing with difficulties or Adversity Quotient (AQ). There are 3 types of AQ namely climber, camper, and quitter. The purpose of this research was to describe the profile of abstract thinking ability in grade VIII junior high school in solving problems in terms of AQ. The type of this research is qualitative descriptive research. The data sourch for this research were 3 students of class VIII-A at SMPN 54 Surabaya with different types of AQ and high mathematical abilities. The instruments used were Adversity Response Profile (ARP) test, abstract thinking ability test, and interview. The result showed that the profile of the climber student’s abstract thinking abilities in solving mathematical problem had reached the level of perceptual abstraction, internalization, interiorization, and second level of interiorization. The camper student’s abstract thinking abilities in solving mathematical problem had reached the level of perceptual abstraction, internalization, interiorization, and second level of interiorization although there are some drawbacks. The quitter student’s abstract thinking abilities in solving mathematical problem had reached the level of perceptual abstraction only.